A randomized Phase 2 study to evaluate the orexin-2 receptor antagonist seltorexant in individuals with insomnia without psychiatric comorbidity. (June 2018) - De Boer, Peter; Drevets, Wayne C; Rofael, Hany; van der Ark, Peter; Kent, Justine M; Kezic, Iva; Parapatics, Silvia; Dorffner, Georg; van Gerven, Joop; Beneš, Heike; Keicher, Christian; Jahn, Holger; et al.
Background: Seltorexant is a potent and selective antagonist of the orexin-2 receptor that is being developed for the treatment of insomnia and major depressive disorder. Aims: The primary objective was to investigate the effect of seltorexant on sleep efficiency after single and multiple dose administration in subjects with insomnia disorder without psychiatric comorbidity. Secondary objectives included evaluation of total sleep time, latency to persistent sleep, and wake after sleep onset. Subjects received 40 mg of seltorexant for five days during Period 1 and placebo during Period 2 or vice versa in this randomized, two-way crossover study. Objective sleep parameters were evaluated by polysomnography over 8 h on Day 1/2 (single dose) and on Day 5/6 (multiple doses). Subjective sleep parameters were assessed by questionnaires. Results: Twenty-seven subjects completed the study. The mean changes in sleep efficiency (% (SD)) of seltorexant from placebo at Day 1/2 were 5.8 (9.2), and 7.9 (9.8) at Day 5/6 ( p < 0.001 at both time points); in total sleep time (min (SD)) 27.7 (44.3) and 37.9 (47.1), respectively; in latency to persistent sleep (min (SD)) −18.8 (21.3) and −29.9 (27.7), respectively; and in wake after sleep onset (min (SD)) −11.1 (36.4) and −11.3 (46.5). The most common adverse events were headache and somnolence. Conclusions: Sleep efficiency was increased with seltorexant treatment compared with placebo. Treatment with seltorexant resulted in a prolonged total sleep time, shorter latency to persistent sleep and wake after sleep onset. There were no unexpected safety findings.